Design of Wireless Sensor Network for Internet of Things Structure - Cetin, Ramazan; Kadioglu, Tevfik; Cesur, Evren; Ayten, Umut Engin (IEEE, 2016)
In this study, a wireless sensor network design for internet of things (IoT) is realized. The designed system consists of a sensor node that contains lots of sensors and a sensor gateway. Sensor gateway connects sensor node to the internet. Sensor nodes collect variety of real world data, than transmits these data into sensor gateways using ZigBee wireless communication protocol. Sensor gateway sends these data into cloud through Wi-Fi module which is a part of the sensor gateway. Data can be observed by the cloud system on the internet, also all systems can be managed from sensor gateway to the sensor node.
Keywords: Engineering